1982
DOI: 10.1007/bf01415883
|View full text |Cite
|
Sign up to set email alerts
|

Beta-decay energies and nuclear masses of very neutron-rich Rb and Cs isotopes

Abstract: The /?-endpoint energies of very neutron-rich Rb and Cs isotopes with mass numbers 94_< A < 98 and 142_ A_< 146, respectively, have been measured with a plastic scintillator/?-telescope at the on-line mass separator OSTIS. From these, Q~-values and mass excesses are calculated and compared with the results obtained in direct mass determinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The two groups around 2.1MeV and 4.2MeV have rather low /?-feeding, whereas the third group of levels at about 3.5 MeV is strongly populated. The log ft values calculated with a /?-decay energy of Q~=(9,255 +70)keV [24] indicate that the /?-branches to the low-lying levels in 95Sr are first-forbidden. The levels around 3.5 MeV, however, are fed by allowed transitions.…”
Section: Resultsmentioning
confidence: 99%
“…The two groups around 2.1MeV and 4.2MeV have rather low /?-feeding, whereas the third group of levels at about 3.5 MeV is strongly populated. The log ft values calculated with a /?-decay energy of Q~=(9,255 +70)keV [24] indicate that the /?-branches to the low-lying levels in 95Sr are first-forbidden. The levels around 3.5 MeV, however, are fed by allowed transitions.…”
Section: Resultsmentioning
confidence: 99%
“…The large errors allow spin 2 (positive parity) for this level confirmed by the value given in [24]. This state is a good candidate for the one- 1&55.7-1&4.5…”
Section: Kev Levelmentioning
confidence: 86%
“…A simple phenomenological coexistence model [7] gave a good discription of these lower levels of 98Sr and predictions for levels up to 900 keV. Also observed was the delayed neutron emission with a probability of (18.4_+2.9)% [8] as well as the Q~-value of (12440_+110)keV [9][10][11]. Further measurements at OSTIS [7,8] indicated the existence of two isomers of 98Rb with slightly different half-lives of (96_+8)ms and (114 _+ 13) ms, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1 and Table 1, the levels with spin and parity 2 + and 1 are populated by /L decay from the ground state of ~46Cs; in our earlier study [11], also a very weak branch to the 3-level had been observed. No population of the 4 + level has been found in both investigations; therefore, the ground state of ~6Cs should have a low spin value.…”
Section: ~~mentioning
confidence: 89%
“…Therefore, in addition to the new Q~-measurements described above, some /?-decay energies obtained in earlier studies [5,6,8] have been re-evaluated. In this new evaluation, an improved data handling procedure to decompose the complex /?-spectra and to subtract the background was applied, which had been developed in the meantime [11].…”
Section: ~*'71n 57~d90mentioning
confidence: 99%